Optimal model reference adaptive control of spar-type floating wind turbine based on simulated annealing algorithm. (1st July 2022) - Mu, Anle; Huang, Zebo; Liu, Anbang; Wang, Jiahui; Yang, Bin; Qian, Ye
Abstract: Carbon neutrality has led to an explosion in renewable energy, such as floating wind turbine (FWT). However, stability and safety become the main bottleneck in the development of FWTs. In this paper, an active vibration control system is designed to improve the stability of Spar-type FWT. The dynamic model of Spar-type FWT was established, and the model was linearized according to the actual situation of wind turbine. The vibration control of wind turbine structure is analyzed by using tuned mass damper (TMD) active control and the designed active linear quadratic regulator (LQR) algorithm. The weight of LQR controller is designed by simulated annealing (SA) algorithm to eliminate the subjectivity of parameter selection. The analysis shows that compared with the wind turbine system under the passive control system, the deflection angular displacement of the tower of the wind turbine decreases by 80.4% and the deflection angular velocity decreases by 67.6%. The deflection angular displacement of Spar platform decreased by 47.2% and the deflection angular velocity decreased by 37.7%. The optimal model reference adaptive control (MRAC) is designed to solve the uncertainty of structural parameters and loads of wind turbine system. Simulation results show that the proposed method can accurately and quickly track the optimal trajectory with SA-LQR control as the reference model, and realize the real-time optimal control of Spar-type FWT vibration system. All the results show that the method reported here can greatly improve the stability and safety of Spar-type FWTs. Highlights: An optimal adaptive control method based on model reference was proposed for stability of spar-type FWT. The LQR controller of is designed, and the weight of LQR controller is analyzed by simulated annealing algorithm. The optimal control track under the nominal system can be accurately tracked in the case where the parameter is uncertain.